2010
DOI: 10.1523/jneurosci.5168-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Context Integration Mechanisms Underlying Figure–Ground Organization in the Visual Cortex

Abstract: Most neurons in visual cortex respond to contrast borders and are orientation selective, and some are also selective for which side of a border is figure and which side is ground ("border ownership coding").

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
133
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(145 citation statements)
references
References 42 publications
12
133
0
Order By: Relevance
“…Even the more optimistic prediction of 55 ms, which is based on the fictitious assumption that the context influence comes mainly from the closest discriminative feature, is far outside the acceptable range. We call this assumption fictitious, because experiments show that all segments of the figure contours contribute about equally to the DOF signal and that the contribution of close segments is not faster than that of far segments (Zhang and von der Heydt 2010).…”
Section: The Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even the more optimistic prediction of 55 ms, which is based on the fictitious assumption that the context influence comes mainly from the closest discriminative feature, is far outside the acceptable range. We call this assumption fictitious, because experiments show that all segments of the figure contours contribute about equally to the DOF signal and that the contribution of close segments is not faster than that of far segments (Zhang and von der Heydt 2010).…”
Section: The Experimental Resultsmentioning
confidence: 99%
“…Thus a neuron that is not activated by the figure contour cannot produce spikes and therefore cannot relay information. [The infrequent neurons that are activated by the interior of the figures (Friedman et al 2003) probably do not participate, because experiments have shown that the DOF signal is essentially the same for contour-defined figures as for filled figures (Zhang and von der Heydt 2010), and the former do not activate interior neurons.] The distance to contextual information in the opposite hemisphere was calculated by adding one extra relay of 5 mm for the interhemispheric connection (being interested in the delays rather than the distances, we reasoned that the path through the corpus callosum, although longer, should take about the same time as a relay within the cortex, because the callosal fibers are faster).…”
Section: Context-defined Border Ownershipmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, there is psychophysical evidence indicating that attention (Peterson & Gibson, 1991) and context, such as the familiarity of the shapes of the figures (Peterson & Gibson, 1994;Peterson, Harvey, & Weidenbacher, 1991), can influence the alternation of figure-ground perception in face-or-vase type images. Importantly, a thorough analysis of the temporal properties of the neural activities reported in the series of papers by von der Heydt's laboratory indicates that the very fast signal processing in the BOWN computation can be done only by the feedforward-feedback loops not by the horizontal connections (Craft et al, 2007;Sugihara, Qiu, & von der Heydt, 2011;Zhang & von der Heydt, 2010;Zhou et al, 2000).…”
Section: Implications: How Is Completion Linked To Neural Activities?mentioning
confidence: 99%
“…Acting appropriately in social interactions requires the interpretation of explicit and implicit contextual clues that orient our responses toward being polite, to make a joke or point out an irony, to say or not say something. Cognitive science and neuroscience research have evidenced context-dependence effects in similar domains of visual perception, [1][2][3] emotion, 4 -7 language, 8 -14 and social cognition 15,16 in both normal and neuropsychiatric conditions. But what is context?…”
mentioning
confidence: 99%